Endocrine Surgery and Pediatic Surgery Partnership Reduces Complication Rate of Pediatric Thyroidectomy - Ali Sayan; Mehmet Üstün; Mehmet Mert; Cem Karaali; Gökhan Köylüoğlu (Galenos Publishing House, 2022)
Objective: Thyroidectomy is not a common procedure performed in childhood. The aim of this study is to evaluate the clinical data and postoperative results of pediatric patients who underwent thyroidectomy in our center performed by a pediatric and an endocrine surgeon working in collaboration. Method: Patients under the age of 18 who underwent thyroidectomy between 2008-2020 were included in this study. Demographic data, clinical data, preoperative evaluation results and postoperative complications were reviewed retrospectively. Results: A total of 21 patients were included in the study. Postoperative bleeding, surgical site infection, transient and permanent recurrent nerve palsy, and permanent hypocalcemia were not detected in any patient. Transient hypocalcemia developed in only 2 patients (9.5%) in the postoperative period. Conclusion: Small sample size and avoiding central neck dissection may also be effective in our low postoperative complication rate. However, it was thought that pediatric thyroidectomy procedure performed by a general surgeon and a pediatric surgeon experienced in endocrine surgery in collaboration may change the postoperative complication rate.